Investigations of Inflammatory Mechanisms Contributing to the Pathogenesis of SLE in a Western Australian Population - Margery-Muir, Audrey (Curtin University, 2018)
This project focused on the interpretation of a panel of laboratory investigations used in the diagnosis and management of SLE patients in the light of an hypothesis postulating aberrant apoptotic processing of cellular debris. The study included cell analysis, serological assays and genomic typing at the complement C4 loci. It is expected that the results obtained will assist clinicians in the diagnosis and ongoing treatment and monitoring of SLE patients in Western Australia and elsewhere.